Weight Loss in Idiopathic Intracranial Hypertension: A Retrospective Review of Outcomes in the Clinical Setting. Issue 4 (December 2021) - Ang, Juan Lyn; Teo, Kai Z.; Fraser, Clare L.
Abstract : Background: Weight loss is important in the management of idiopathic intracranial hypertension (IIH); however, extremely caloric restrictive diets have been used in published studies, which may not be practical for all patients. We aim to review the weight loss outcomes of IIH patients and weight loss methods used by patients who achieve clinical remission (CR) in a standard clinical setting. Methods: The medical records of IIH patients were retrospectively reviewed. Measures evaluated included: reported symptoms, visual acuity, retinal nerve fiber layer analysis, automated visual fields, optic disc appearance, and cessation of medications. Patients were divided into different outcome groups and weight changes were compared. Patients who achieved CR were contacted to assess weight loss methods used. Results: Of the 39 patients included in the analysis, 28 patients (71.8%) achieved CR with concomitant weight loss, 6 patients (15.4%) improved clinically with concomitant weight loss but did not achieve CR. Among the patients with CR, 10 patients (35.7%) were successfully weaned off their medications completely, whereas another 10 patients (35.7%) are in the process of this. Median weight loss from baseline to lowest weight for this group was 10.5 kg (11.5%) achieved using self-directed methods. Conclusion: This study demonstrated that a large proportion of IIH patients were able to achieve CR or improvement with self-directed weight loss regimens, reinforcing the evidence and the practicality of weight loss in the management of IIH in the clinical setting.